2011
DOI: 10.1111/j.1538-7836.2010.04144.x
|View full text |Cite
|
Sign up to set email alerts
|

Variable effect of P2Y12 inhibition on platelet thrombus volume in flowing blood

Abstract: Summary. Background and objectives: Patients treated with percutaneous coronary intervention receive aspirin and P2Y12 ADP receptor inhibitors to reduce thrombotic complications. The choice of methodology for monitoring the effects of treatment and assessing its efficacy is still a topic of debate. We evaluated how decreased P2Y12 function influences platelet aggregate (thrombus) size measured ex vivo. Methods and results: We used confocal videomicroscopy to measure in real time the volume of platelet thrombi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 47 publications
7
23
0
Order By: Relevance
“…Second, it has become clear from clinical conditions such as unstable angina and from experiments in animals such as those using the Folts model that platelet factors exist that mediate or inhibit thrombus stability. Our data obtained in blood from healthy volunteers confirmed the fact the clinical efficacy of the state-of-the art antiplatelet therapy (clopidogrel + aspirin) utilized in the management of post-atherothrombotic events certainly stems from a synergism in destabilization activities of the two drugs [11,12,24]. They also suggested that high levels of inhibition of the P2Y 12 receptor may be sufficient to provide substantial benefits in agreement with others [17,25].…”
Section: Resultssupporting
confidence: 86%
“…Second, it has become clear from clinical conditions such as unstable angina and from experiments in animals such as those using the Folts model that platelet factors exist that mediate or inhibit thrombus stability. Our data obtained in blood from healthy volunteers confirmed the fact the clinical efficacy of the state-of-the art antiplatelet therapy (clopidogrel + aspirin) utilized in the management of post-atherothrombotic events certainly stems from a synergism in destabilization activities of the two drugs [11,12,24]. They also suggested that high levels of inhibition of the P2Y 12 receptor may be sufficient to provide substantial benefits in agreement with others [17,25].…”
Section: Resultssupporting
confidence: 86%
“…We report findings with some similarities and differences to the prior flow studies of Lucitt et al [17] and Menolicchio et al [18]. Lucitt et al found no effect on the rate of platelet coverage of the collagen surface with in vitro ASA addition at 1500 s −1 .…”
Section: Discussionsupporting
confidence: 82%
“…Similar results were observed in a mouse model of atherothrombosis, where pre-treatment with the P2Y 12 antagonists ticagrelor or cangrelor could not only inhibit thrombus formation, but also decrease its stability [66]. Similar results were observed in ex vivo thrombus formation with human platelets from coronary heart disease patients treated with clopidogrel [67], further confirming the important role of P2Y 12 during thrombus formation and its stability.…”
Section: The Pharmacology Of P2y12 Receptorsupporting
confidence: 75%